Reconstruction of Sharia Understanding with the Humanistic Paradigm: Formulating Khaled Abou El Fadl's Idea of Sharia with the Norm Leveling Theory - Nur Kholis; Qaem Aulassyahied (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2023)
This paper examines Khaled Abou El Fadl’s thoughts that focus on applying humanistic Sharia. Khaled considers the spread of Sharia with a humanistic pattern important because of the problem of not realizing the ideals of Islamic teachings that uphold justice, welfare, and other universal values at the level of reality for Muslims who experience backwardness and alienation. According to Khaled, this happened due to a misunderstanding in understanding the Sharia, resulting in a wrong practice. The misunderstanding that gave rise to this wrong practice has global implications, assuming that Islam is a non-humanistic religion. By using the analytical description method, this paper reformulates the humanistic Sharia proposed by Khaled from several of his works and rearranges it based on the theory of the leveling norms.